2018
DOI: 10.1080/03639045.2018.1430820
|View full text |Cite|
|
Sign up to set email alerts
|

Dual effect biodegradable ciprofloxacin loaded implantable matrices for osteomyelitis: controlled release and osteointegration

Abstract: Ciprofloxacin biodegradable implantable matrices (CPX-IMs) of tailored porous surfaces were fabricated by hot melt injection molding of poly-l-lactic acid (PLLA) followed by coating with PLLA/sodium chloride. CPX-IDs were designed to have a non-porous coat (NPC) or a porous coat of small pore size (SPC; 150-250 µm) or a large pore size (LPC; 250-350 µm). CPX-IMs surface pore size was confirmed by scanning electron microscope. The hardness of NPC, LPC, and SPC CPX-IMs were 58 ± 2.8, 53 ± 1.9, and 50 ± 2.1 N, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Finally, bone-cement monomers, such as PMMA, are moderately toxic. To circumvent these shortcomings, absorbable biomaterials [8][9][10][11][12][13][14] have been used to replace bone cement (e.g. PMMA) in the treatment of chronic osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, bone-cement monomers, such as PMMA, are moderately toxic. To circumvent these shortcomings, absorbable biomaterials [8][9][10][11][12][13][14] have been used to replace bone cement (e.g. PMMA) in the treatment of chronic osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, other antibiotics, such as imipenem/cilastatina (Tienam) [ 79 ] or a combination of gentamicin and clindamycin [ 81 ], were also used in scaffolds. Additional coatings were created by mixing levofloxacin with gold [ 90 ] and ciprofloxacin with PLLA and NaCl [ 91 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the in vivo studies complemented by in vitro relevant data on microbiology analysis, only one study reported previously established infection in animals before implantation (10 days) [ 84 ]. Moreover, one article evaluated the presence of infection in vivo, even though no animals had been intentionally infected [ 91 ]. The remaining studies did not address infection in vivo [ 68 , 76 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dip-coating is the simplest technique that does not require substantial machinery and equipment [ 17 ]. In this method, the porous scaffold is dipped into the coating solution containing a specific drug-like chemical that would allow the ceramic scaffold to act as a carrier for the drug delivery system [ 18 , 19 , 20 ]. Many studies have demonstrated that scaffolds coated with the drug solution using the dip-coating technique are effective for bone tissue engineering [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%